A new species of pygmy crickets and synonyms of a genus and a species of sword-tail crickets (Orthoptera: Trigonidiidae: Nemobiinae and Trigonidiinae) from China - Wu, Qian; Ma, Li-Bin (Zootaxa, 2022)
Here, we describe a new species of the genus Polionemobius from Wuyanling Nature Reserve, Zhejiang Province of China. Meanwhile, we have confirmed two new synonyms. The genus Polycomus is a junior synonym of the genus Zilingxi, and Polycomus exspiravit He & Ma, 2022 is a junior synonym of Zilingxi dian He, 2022.